Prevalence and Determinants of Malnutrition among Under-five Children of Farming Households in Nigeria - Sowunmi, Fatai Abiola; Ese, Peace; Adejoorin, Mobolaji; Omotayo, Abiodun Olusola; Salman, Kabir Kayode (HABITAT, 2024)
The prevalence of child malnutrition among farming households in rural Nigeria is a burden to the economy now and in the future. Secondary data was employed in the study, collected from the Nigeria Demographic and Health Survey (NDHS) for 2018 conducted by the National Population Commission (NPC). The study focused on 3,177 children (0-57 months) whose fathers were employed in agriculture. Descriptive statistics, probit regression, and the Analysis of Variance (ANOVA) were utilised. The study affirmed moderately high child malnutrition in Nigeria. The disaggregation revealed that the northern zone (55.31%) had higher child malnutrition than the southern zone (32.19%). The likelihood that a child selected at random would be malnourished was higher in the northern geopolitical zones. The higher child malnutrition rate in the northwest than in the northeast geopolitical zone posited that insecurity alone did not cause child malnutrition among rural farming households in Nigeria. There was significant variation in child malnutrition status among the geopolitical zones. Household size, mother’s education and household economic status influenced child malnutrition in the Northeast, northwest, and northcentral, respectively. Additionally, distance to healthcare facilities, mother’s age and mothers’ engagement in agriculture drive child malnutrition in the northcentral, northeast and southern geopolitical zones. Consequently, training of unemployed mothers in craft making and processing of agricultural produce (northcentral and southern zone) to enhance household income by NGOs, intensification of the family planning campaign (northcentral and northeast) by NGOs and health Department of Local Government Area and basic/adult education (northwest) are the geopolitical zones’ specific recommendations to reduce child malnutrition in Nigeria.